PENGARUH UKURAN PERUSAHAAN, AUDITOR SWITCHING DAN AUDIT FEE TERHADAP AUDIT DELAY PADA PERUSAHAAN PROPERTI YANG TERDAFTAR DI ISSI PERIODE 2016-2020 - Rabaiyah; Elyanti Rosmanidar; Nurfitri Martaliah (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2023)
Audit Delay is the time span for the completion of the annual financial statement audit. Completion of financial statement audits may experience delays caused by several factors such as company size, auditor switching, and audit fees. This study aims to analyze the effect of Company Size, Auditor Switching and Audit Fee on Audit Delay in property companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2016-2020 period. The data used is secondary data with the panel data regression analysis method with the help of the e-view 12 program to see a comprehensive picture of the independent variables on the dependent variable. The sample in this study consisted of 9 companies for 5 years. The results of this study indicate that firm size has a negative and insignificant effect on audit delay with a significance level of 0.372 > 0.05. Auditor switching has a positive and significant effect on audit delay with a significance level of 0.032 <0.05. Audit Fee has a significant effect on audit delay with a significance level of 0.045 < 0.05. While the company, auditor switching and audit fees together affect the audit delay variable with a significance value of 0.018 <0.05. The magnitude of the influence of company size, auditor switching and audit fees on audit delay as a whole is 24%